FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MODERASI - Dewita, Laurencia; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence regarding the effect of profitability, liquidity, and leverage on firm value with corporate social responsibility as a moderating variable in non-cyclicals sector companies listed on the Indonesia Stock Exchange during the period 2019 until 2021. This study uses secondary data. Data processing in this study uses the program E-views version 12.0. The sampling technique used is purposive sampling and obtained as many as 23 companies that meet the criteria. The results showed that profitability and liquidity did not have a positive effect on firm value, and leverage and corporate social responsibility did not have a negative effect on firm value. Corporate social responsibility cannot moderate the effect of liquidity and leverage on firm value.